Toward the design of efficient transglycosidases: the case of the GH1 of Thermus thermophilus. Issue 7 (11th October 2019) - David, Benoit; Arnaud, Philippe; Tellier, Charles; Sanejouand, Yves-Henri
Abstract: Using the information available in the sequences of well-characterized transglycosidases found in plants, mutations were introduced in the glycoside hydrolase of the bacterium Thermus thermophilus, with the aim of turning it into an efficient transglycosidase. All mutants happen to have fair catalytic efficiencies, being at worst 25 times less efficient than the wild type. Noteworthy, W120F, one of our high transglycosylation yield (≈ 50%) mutants, is only two times less efficient than the wild type. Interestingly, while in the wild type the sidechain of the acid–base is only found able to sample a pair of equivalent conformations during 0.5-μs-long molecular dynamics simulations, its flexibility is much higher in the case of the high transglycosylation yield mutants. Our results thus suggest that engineering the flexibility of the acid–base of a retaining glycoside hydrolase could be a general way to turn it into an efficient transglycosidase.